STRATEGI KOMUNIKASI PEMASARAN DIGITAL UNTUK MENINGKATKAN BRAND LOYALTY PADA PERUSAHAAN TRAVEL DI MASA PANDEMI COVID-19 (Studi Kasus pada CV. Khairil Tour & Travel) - Arina Muntazah; Novalia Novalia; Rindana Intan Emeilia (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
Travel companies during the Covid-19 pandemic faced challenges that were not easy to deal with, given the large-scale social restriction regulations which resulted in limited use of travel services for tourism. This study aims to determine the implementation of digital marketing communication strategies in travel companies during the Covid-19 pandemic at CV. Khairil Tour & Travel. This study uses a qualitative approach with research methods, namely case studies. Data obtained by collecting supporting theories and conducting in-depth interviews with company owners. From the results obtained, in increasing brand loyalty, CV Khairil Tour & Travel implemented a digital marketing communication strategy through several social media, those are Instagram, Facebook, WhatsApp and Youtube with promotional content such as pictorial messages in the form of digital posters containing product photos (tours object), information on travel times, contact persons, and additional information regarding the Covid-19 prevention protocol that is still being considered.